Piperidines as dual inhibitors of tyrosinase and pancreatic lipase: in vitro and in silico mechanistic insights - Naeem, Nafeesa; Mughal, Ehsan Ullah; Shakoor, Bushra; Sadiq, Amina; Othman, Gehan Ahmed; Bursal, Ercan; Yetissin, Fuat (Taylor & Francis Ltd, 2025)
AimsThis study aimed to explore the dual inhibitory potential of a series of piperidine derivatives against tyrosinase and pancreatic lipase. For the first time, these compounds were evaluated concurrently for their inhibitory effects on both enzymes, targeting potential therapeutic applications in hyperpigmentation and obesity-related disorders.Materials and methodsA total of eight piperidine-based compounds were synthesized and assessed for in vitro inhibitory activity against mushroom tyrosinase and pancreatic lipase. The most active derivatives underwent kinetic studies to determine the mode of inhibition using Lineweaver-Burk plots. Structure-activity relationship (SAR) analysis was performed to identify key substituents influencing bioactivity. Furthermore, molecular docking, molecular dynamics (MD) simulations, and density functional theory (DFT) calculations were conducted to elucidate the binding interactions and electronic properties associated with inhibition.ResultsAmong the tested compounds, several exhibited significant dual inhibitory activity, with low micromolar IC50 values against both enzymes. Kinetic analysis revealed competitive inhibition for the lead compound. Docking and MD simulations confirmed stable binding within the active sites of both enzymes, supported by favorable DFT descriptors.ConclusionsThese findings reveal, for the first time, that piperidine derivatives possess promising dual inhibitory activity against tyrosinase and pancreatic lipase, supported by both experimental and computational evidence.
Keywords: Piperidine; tyrosinase; pancreatic lipase; in vitro; molecular docking; MD simulation; DFT; ADMET